Создание основы для нового теплоизоляционного материала - Чейлытко, Андрей Александрович; Павленко, Анатолий Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
Work examines and analyzed raw basis for creating the new heater. The indices of quality of raw material and the prescription- technological parameters are given. Are also given the values of the parameters of the drying of basis in the vortex flow for obtaining the minimum thermal conductivity of material.